Determinants of Hypertension: A Cross-Sectional Analysis of Demographic and Physiological Predictors in a Referral Hospital in Iran - Fatemeh Omidi; Soheila Sadeghi (Novelty in Biomedicine)
Background: Hypertension is a leading risk factor for cardiovascular diseases, significantly contributing to global morbidity and mortality. Understanding the determinants of hypertension is crucial for effective prevention and management. This study investigates the relationships between demographic and physiological factors and hypertension status in a cohort of adults.